A comparison between Malaysia and Singapore stock index: macroeconomic variable / Nurul Natashya Taib - Taib, Nurul Natashya (Faculty of Business Management, 2017)
The paper analyzes a comparison between Malaysia’s and Singapore’s stock index towards macroeconomic variables such as interest rate, consumer price index, exchange rate, and gross domestic product. For these case using time series techniques of cointegration and vector autoregression. In the analysis, we rely on variance decompositions and impulse response functions to gauge the strength of the interactions among the variables. The data selected for these cases consists of annually data from stock index market from KLCI and STI. The lending rate is base on study the interest rate, exchange rate represent by Malaysia Ringgit (MYR) to US Dollar (USD) and Singapore Dollar (SGD) to US Dollar (USD), consumer price index (CPI) represent inflation and gross domestic product (GDP) represent the growth economy of country. The data will be collect and gathered for evaluate and compare to find the significant results of the study. The research consists period of 35 years with annually data analysis from 1980-2015. In addition, this research can be a good guide and produce accurate results to the individuals who want to make an investment decision. The person who wants to participate in the stock market also can use this result for their guidelines when he or she wants to make an investment trading.